2022
DOI: 10.1038/s41598-022-11354-x
|View full text |Cite
|
Sign up to set email alerts
|

Brønsted acidity in zeolites measured by deprotonation energy

Abstract: Acid forms of zeolites have been used in industry for several decades but scaling the strength of their acid centers is still an unresolved and intensely debated issue. In this paper, the Brønsted acidity strength in aluminosilicates measured by their deprotonation energy (DPE) was investigated for FAU, CHA, IFR, MOR, FER, MFI, and TON zeolites by means of periodic and cluster calculations at the density functional theory (DFT) level. The main drawback of the periodic DFT is that it does not provide reliable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…The DPEs are the energy differences between the deprotonated and protonated cluster models. [57][58][59][60] The calculated numbers are large compared to a typical bond energy (given as the energy for a homolytic bond scission), because the heterolytic reactions include charge separation, and this artificial Coulomb contribution is substantial. However, DPEs can be useful, if they are applied for a comparison of similar chemical moieties regarding their acidity differences.…”
Section: Calculationsmentioning
confidence: 99%
“…The DPEs are the energy differences between the deprotonated and protonated cluster models. [57][58][59][60] The calculated numbers are large compared to a typical bond energy (given as the energy for a homolytic bond scission), because the heterolytic reactions include charge separation, and this artificial Coulomb contribution is substantial. However, DPEs can be useful, if they are applied for a comparison of similar chemical moieties regarding their acidity differences.…”
Section: Calculationsmentioning
confidence: 99%
“…[14][15][16] The acid strength of protons in zeolites depends on the zeolite topology, composition and proton location in specic crystallographic positions. 12,17,18 However, the relation of proton acid strength and concentration on the catalytic activity is not straightforward, 10 also in relation to proton mobility, 19 which can be mediated by interaction with reactants or adsorbed molecules, such as water 17,20,21 or ammonia. [22][23][24] Metal cations are stabilized in specic crystallographic positions in the channels and cages of zeolites, depending on the nature of the metal cation combined with the topology and chemical composition of the material.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] Another fascinating aspect of the inner structure of zeolites is that it can stabilize cations in geometries and even oxidation states which are not usually observed in solids, solution or homogeneous complexes. 8,9 Protons represent a particular and important class of cations stabilized in zeolites, conferring them a specic Brønsted acidity, [10][11][12][13] which is crucial for many applications. [14][15][16] The acid strength of protons in zeolites depends on the zeolite topology, composition and proton location in specic crystallographic positions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They attributed the invariance of intrinsic barriers to similar acid-site strengths for Al-substituted Brønsted-acid sites across different regions . However, it should be noted that intrinsic acid-site strengths, as typically equated with their deprotonation energies, are hard to quantify unambiguously. Theoretical calculations consistently found appreciable site and structure sensitivities, the magnitude of which is reduced only after accounting for the varying T-site densities and the resulting differences in the dielectric constants of the materials . Gounder and Iglesia also concluded that intrinsic barriers remained similar across different alkane chain lengths, based upon the adsorption enthalpies measured at low temperatures and extrapolated to the cracking temperatures. , The same conclusion was reached by Li et al Gorte and co-workers studied the endothermic cracking of n -hexane in H-ZSM-5, H-BEA, H-MOR, and USY zeolites and found that a single rate expression was able to describe the kinetics over a very wide range of pressures. , The temperature dependence of rate constants was again identified to the adsorption enthalpies of n -hexane. , Kadam et al studied the protolytic cracking reaction of propane and n -butane in the FER, TON, MFI, and CHA zeolites at temperatures ranging from 580 to 710 K and observed that intrinsic activation barriers are insensitive to the zeolite structure.…”
Section: Introductionmentioning
confidence: 99%